Karakteristik Habitat Aedes aegypti (L) di Wilayah Perimeter Pelabuhan Laut Cirebon, Jawa Barat (CHARACTERISTICS OF AEDES AEGYPTI (L) HABITAT IN CIREBON SEA PORT REGION, WEST JAVA) - Affiandy, Dudy; Amin, Akhmad Arif; Ridwan, Yusuf (Jurnal Veteriner, 2019)
Vector infectious diseases such as Dengue Hemorrhagic Fever (DHF) are still a major health problem in Indonesia including Cirebon City. Cirebon seaport as one of the country’s entrances has the potential to transmit dengue disease. The aim of the study was to measure the population density of Aedes aegypti larvae and analyze the relationship of habitat characteristics with the presence of Ae. aegypti larvae in the perimeter region of Cirebon seaport. Analytic descriptive observation with a cross sectional study approach was conducted in the study. The sample were all the houses/ buildings in the perimeter region of Cirebon seaport are used as breeding habitats for Ae. aegypti. The results of the study, the types of positive containers of Ae. aegypti larvae are water closet (WC) tanks, bathtubs, drums, pails, ponds and used tires. Calculation results of the House Index (HI), Container Index (CI), Breteau Index (BI) and Density Figure (DF) (HI: 8.74%; CI: 9.05%; BI: 12.02; DF: 3). Based on chi square test, habitat characteristics that have a significant relationship with the presence of Ae. aegypti larvae were container type, container material, water volume, water source, water pH and air temperature (p<0.05). The results of the analysis with binary logistic regression had a significant effect on the presence of Ae. aegypti larvae, namely in pails (p=0.003; OR=18.972) and water pH (p=0.022; OR=2.489). Conclusion of the study is Cirebon seaport area has a risk of dengue transmission at a moderate level based on its vector density.